Breakthrough and episodic pain in cancer patients – a new look - Leppert, Wojciech; Forycka, Maria; Nosek, Krzysztof (Medycyna Paliatywna/Palliative Medicine, 2016)
Breakthrough pain in cancer patients (BTCP) called episodic or incident pain appears in significant percentage of patients (40–60%). BTCP is characterised by quick intensifying (within seconds or minutes), significant intensity (NRS over 5) and limited time (most frequently up to 30 minutes). Clinically 2 types of BTCP were found: spontaneous (idiopathic) diagnosed when the cause of pain is unknown and incident pain evoked by activities; the latter is further divided into 2 subtypes: involuntary, when pain is evoked independently on patients will and voluntary associated with activity dependent on patients. In spontaneous or incident involuntary pain treatment is based on analgesics (most frequently opioids) with a quick onset of action administered when pain is intensifying – fentanyl formulations administered by intranasal, buccal or sublingual route. In predicted pain episodes more frequently immediate–release opioid formulations are administered by oral or parenteral route. The strategy of BTCP management should be based on precise diagnosis of pain type and therapy directed at pain cause and patomechanism. A key element is precise pain assessment in the context of other symptoms, psychological, social and spiritual problems of patients and careers and introduction of effective therapy that considers causes of pain. Complex management may render effective pain treatment and improvement of patients’ and families’ quality of life. In this article BTCP management is outlined paying attention to appropriate clinical evaluation of pain, introduction of episodic pain term as broader concept than BTCP and individual approach to patients considering their preferences and satisfaction from BTCP treatment.